Contributions of Tiku Fishing Port (PPI Tiku) for fisheries sector at Agam regency, West Sumatera province, Indonesia - Dongoran, Erly Novida; Zain, Jonny; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Purpose of this research is to know the role of fishing port for giving contribution at fisheries sector in Agam regency, west Sumatera province. A series survey activitywas conducted to evaluate the development of fisheries sector at Tiku regency with the presence a fishing port at Tiku village. The data was analyzed by percentage (%) calculation of fish production at tiku fishing port, further to compare with fish production data at Agam regency. The result shows that the Tiku fishing port was given an incremental number of fishing boat at Agam regency as 43.92-54.69%. The number of fishermen was increased as 53.75- 69.84%, and the number of fishing gear was given contribution as 46.20-68.79%. The total fish production was given small contributionas 28.33-7.58% or smaller than 50%.Keywords: Agam regency, contribution, fisheries sector, Tiku fishing port